Effects of a rooftop wind turbine on the dispersion of air pollutant behind a cube-shaped building - Shuaibin Zhang (Elsevier, 2021)
The concentration distribution of urban air pollutants is closely related to people's health. As an important utilization form of urban wind power, rooftop wind turbines have been widely used in cities. The wake effect of the rooftop wind turbines will change the flow behind buildings and then affect the pollutant dispersion. To this end, the pollutant dispersion behind the building is studied via the computational fluid dynamics method. The actuator disk model and idealized cube are adopted to model the wind turbine and the building, respectively. The study shows that the rooftop wind turbine can reduce the pollutant mass fraction near the ground and the pedestrian level. Due to the wake effect of the rooftop wind turbine, the turbulent fluctuation behind the building is weakened, and the spanwise pollutant dispersion is suppressed. Besides, the rooftop wind turbine weakens the downwash movement of the building, which enhances the vertical pollutant dispersion.